J Aquac Res Development 2015
DOI: 10.4172/2155-9546.1000390
|View full text |Cite
|
Sign up to set email alerts
|

Survival and Immunity of Marron Cherax cainii (Austin, 2002) Fed Bacillus mycoides Supplemented Diet under Simulated Transport

Abstract: The present study examined the effect of simulated transport on marron, Cherax cainii, (Austin, 2002) after a 10 week feeding trial using basal diet or customised probiotic, Bacillus mycoides supplemented diet by measuring intestinal bacterial population, total haemocyte count (THC), bacteraemia, morbidity, dehydration and mortality.Packing steps followed the established standard packing method for live transportation of marron. Each treatment group consisted of six polystyrene boxes (65 × 30 × 40 cm 3 ), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 59 publications
1
3
0
Order By: Relevance
“…Similar to previous studies [3,5], during air exposure stress, no sign of mortality was detected in all GLP-supplemented and control groups. Consistent with the obtained results, studies conducted on marron (Cherax cainii) fed pre-or probiotic revealed that 24 h subjecting to air [59] as well as 36 h ( [1]) did not alter the survival rate. However, GLP-supplemented crayfish in the present study demonstrated better performance in response to stress due to enhance THC, SGC, HC, and CAT activities compared to the control.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Similar to previous studies [3,5], during air exposure stress, no sign of mortality was detected in all GLP-supplemented and control groups. Consistent with the obtained results, studies conducted on marron (Cherax cainii) fed pre-or probiotic revealed that 24 h subjecting to air [59] as well as 36 h ( [1]) did not alter the survival rate. However, GLP-supplemented crayfish in the present study demonstrated better performance in response to stress due to enhance THC, SGC, HC, and CAT activities compared to the control.…”
Section: Discussionsupporting
confidence: 86%
“…Additionally in a study conducted on marron, different MOS inclusion levels could significantly enhance THC and LGC proportion compared to the unsupplemented group after air exposure ( [1]). Moreover, higher health status in marron fed Bacillus mycoides represented by higher THC levels following air exposure stress [59].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, the production has remained stagnant over the decade (Van Mai & Fotedar, 2018). To improve the production potential, several investigations have been conducted to find the suitable combination of feed for marron (Ambas, Suriawan & Fotedar, 2013; Ambas & Fotedar, 2015; Ambas, Buller & Fotedar, 2015). As an omnivorous animal, the protein requirement for marron is moderate (approximately 30%) (Ambas, Fotedar & Buller, 2017).…”
Section: Introductionmentioning
confidence: 99%